2015
DOI: 10.3892/br.2015.473
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium prevents β-glycerophosphate-induced calcification in rat aortic vascular smooth muscle cells

Abstract: Abstract. Vascular calcification (VC), in which high serum phosphate plays a critical role, is one major problem in patients with chronic kidney disease. Clinical studies report that magnesium has a protective effect on VC. However, the studies regarding the impact of high serum magnesium on VC at a cellular level are few and require further investigation. Therefore, the present study explored the effect of magnesium on calcification induced by β-glycerophosphate (BGP) in rat aortic vascular smooth muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
5
27
0
1
Order By: Relevance
“…CAC has been shown to be associated with left ventricular diastolic dysfunction a major cause of HF with preserved ejection fraction in the elderly [ 29 ]; prospective studies have shown CAC to be associated with increased risk of incident HF [ 30 , 31 ]. Animal and experimental models have shown that magnesium prevents vascular calcification in aortic vascular smooth muscle cells [ 32 , 33 ]. Serum magnesium has been shown to be inversely related to CAC in the general population [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…CAC has been shown to be associated with left ventricular diastolic dysfunction a major cause of HF with preserved ejection fraction in the elderly [ 29 ]; prospective studies have shown CAC to be associated with increased risk of incident HF [ 30 , 31 ]. Animal and experimental models have shown that magnesium prevents vascular calcification in aortic vascular smooth muscle cells [ 32 , 33 ]. Serum magnesium has been shown to be inversely related to CAC in the general population [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium plays an important role in vascular health, with normal magnesium homeostasis in VSMC maintained via TRPM7 cation channels. Magnesium prevents posttranscriptional changes in VSMC differentiation and apoptosis and up‐regulates VC inhibitors (MGP and osteopontin), whilst counteracting expression of osteogenic transcription factors (BMP‐2, RUNX2, Msh homeobox 2, and SRY‐ box 9), bone proteins and genes associated with matrix mineralization (osteocalcin and TNAP) . In animal models of VC, dietary supplementation with magnesium results in marked reduction in VC and mortality, improved mineral metabolism, including lowering of PTH, as well as improvement in renal function …”
Section: Future Potential Management For Vc In Clinical Evaluationmentioning
confidence: 99%
“…During sexual stimulation, the relaxation in the smooth muscles of the arteries that supply blood to erectile tissues is important for erection (26). Studies on this subject have reported that Mg plays an important role in vascular tonus by the Ca-channel blockade in vascular smooth muscle cells (27,28). In addition, the relationship has been reported between reduced Mg levels and abnormal growth of vascular muscle cell, muscle contraction, inflammation, and fibrosis (29).…”
Section: Discussionmentioning
confidence: 99%